Are minimum indoor air quality requirements combined with passive retrofit solutions enough to guarantee thermal comfort in southern Spain High Schools? - Calama-González Carmen María; Escandón Rocío; Suárez Rafael (E3S Web of Conferences)
This study addresses the challenging research gap of assessing whether passive energy retrofit solutions are adequate for simultaneously achieving indoor air quality and thermal comfort in educational buildings, given the minimum ventilation rate required by Spanish regulations. A representative educational building is selected as case study to simulate the performance of the existing high school stock in southern Spain. Then, a multi-objective optimisation approach based on NSGA-II genetic algorithms is used for the evaluation of a range of passive energy retrofit strategies, with the aim of identifying the most effective. The findings indicate that, even though the minimum ventilation rate ensure indoor air quality, it is ineffective to maintain thermal comfort. This study highlights a clear overheating problem, especially in summer, that is aggravated when incorporating insulation to the envelope, given the high internal loads and the difficulty of heat dissipation of the envelope. It is concluded that optimising ventilation according to the seasonal period and applying higher ventilation rates than the ones established in the applicable regulations are crucial for reaching both indoor air quality and thermal comfort only considering passive retrofit solutions.